Transformasi Pendidikan di Pesantren Abad 21 di Pondok Pesantren Riyadus Samawi Ludoyo Blitar - Nur Yanah; Siti Nurlatifah; Anjani Rohmata Robbi (FKIP, Universitas Palangka Raya, 2024)
Globalization is a challenge for Islamic boarding schools, because with globalization, Islamic boarding schools are required to continue to improve the quality of education in the Islamic boarding school. Changes or transformations in Islamic boarding schools are the impact of changes in mindset, social, economic, cultural and mastery of science and technology. The purpose of this service is to provide insight and accompany students about the transformation of 21st century Islamic boarding school education so that students at the Riyadus Samawi Islamic Boarding School can contribute to their Islamic boarding school towards a competitive Islamic boarding school of the future without eliminating the characteristics and culture of the Islamic boarding school. In the PkM process carried out at the Riyadus Samawi Islamic Boarding School, Ludoyo Blitar, there are three stages, including: first, identifying problems with a study carried out by the PkM team, Islamic Boarding School Management, Islamic Boarding School Caretakers, and Islamic boarding school owners to determine the quality and development of education in Islamic boarding schools in this era of globalization. The second stage is the implementation of PkM by holding a seminar with the theme